Role Model Characteristics and Impact of Role Models on Medical Students’ Specialty Choices (Bangladesh Journal of Medical Education, 2022)
This was a descriptive type of cross-sectional study conducted to identify the Characteristics /qualities of role model/ medical teachers as perceived by medical students and to identify the influence of role models in selecting subjects for their future career. This descriptive type of cross-sectional study was conducted during July 2019 to June 2020. A semi-structured, self-administered questionnaire was used to collect data. A total of 868 medical students of phase III and phase IV were the respondents of the study. All available students who were willing to participate in the study were selected and medical colleges were selected purposively. Study revealed that out of 868 respondents 741 (85.4%) had identified role models during the course of their studies and 127 (14.6%) respondents could not identify any role models. It was observed that 91% students opted for clinical subjects while 9% opted for preclinical and para-clinical subjects. With regards to their subjects of choice for future career 21.0% of the students preferred Medicine, followed by Surgery (20.0%), Gynecology (9.2%) and Orthopedics (3.8%).Two hundred and thirty-two (26.7%) of the students did not choose any subject for their future career. Regarding the influence of role models in selecting subjects for future career it was revealed that 334 (61%) respondents felt that role models had influence. Maintaining integrity and neutrality by role models was given the highest importance and general appearance of role model was considered least important by the respondents. (Not clear! is it Role Model Characteristics?).The academic institutes should make an effort to develop the role modeling of faculty by highlighting positive attributes of role models. Teachers should be made aware of the influence of role models on their future colleaguesBangladesh Journal of Medical Education Vol.13(1) January 2022: 3-9